2020
DOI: 10.1101/2020.02.16.951285
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eukaryotic rather than prokaryotic microbiomes change over seasons in rewetted fen peatlands

Abstract: 23Background: Drainage of high-organic peatlands for agricultural purposes has led to increased greenhouse 24 gas emissions and loss of biodiversity. In the last decades, rewetting of peatlands is on the rise worldwide, 25 to mitigate these negative impacts. However, it remains still questionable how rewetting would influence 26 peat microbiota as important drivers of nutrient cycles and ecosystem restoration. Here, we investigate the 27 spatial and temporal dynamics of the diversity, community composition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…No such data are available for Zarnekow, however, given that site conditions typically do not change drastically between July and mid-September, any temporal influence should be negligible compared to the effects of the extreme drought. Finally, Wang et al (2021) found no seasonal variation in prokaryotic microbial community composition in other coastal and riparian fen systems in northeastern Germany.…”
Section: Peat and Porewater Collection (Drought Year)mentioning
confidence: 67%
“…No such data are available for Zarnekow, however, given that site conditions typically do not change drastically between July and mid-September, any temporal influence should be negligible compared to the effects of the extreme drought. Finally, Wang et al (2021) found no seasonal variation in prokaryotic microbial community composition in other coastal and riparian fen systems in northeastern Germany.…”
Section: Peat and Porewater Collection (Drought Year)mentioning
confidence: 67%